1987
DOI: 10.1007/bf01296704
|View full text |Cite
|
Sign up to set email alerts
|

Oral naloxone antagonizes loperamide-induced delay of orocecal transit

Abstract: Orocecal transit time was determined by the lactulose hydrogen breath test in nine healthy volunteers after administration of placebo, loperamide (16 mg per os), and loperamide (16 mg per os) followed by oral naloxone at doses of 16 and 32 mg. The four tests were performed in double-blind conditions and in random sequences. Transit time (mean, SD) after loperamide (128.8 min, 32.9) was significantly increased (P less than 0.05) compared with placebo (85.5 min, 35.7), loperamide followed by naloxone 16 mg (88.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…No ineffectiveness was recorded during this treatment. Loperamide is a selective mu-opiate-receptor agonist that is able to prolong orocecal and colonic transit times by disrupting the gut's electrical activity, increasing gut capacity, and delaying the passage of fluids through the small intestine [35]. Several studies reported that loperamide is able to reduce diarrhea manifestations in adults, with or without antibiotic treatments [36].…”
Section: Discussionmentioning
confidence: 99%
“…No ineffectiveness was recorded during this treatment. Loperamide is a selective mu-opiate-receptor agonist that is able to prolong orocecal and colonic transit times by disrupting the gut's electrical activity, increasing gut capacity, and delaying the passage of fluids through the small intestine [35]. Several studies reported that loperamide is able to reduce diarrhea manifestations in adults, with or without antibiotic treatments [36].…”
Section: Discussionmentioning
confidence: 99%
“…We studied eleven patients (three men, eight women) with irritable bowel syndrome in view of a suggested clinical application of 3-adrenoceptor agonists in these patients (Lyrenas et al, 1985 a (Basilisco et al, 1987). At 09.30 h the fasting subjects ingested 10 g of lactulose suspended in 100 ml of tap water.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the amount of this drug that crosses the blood-brain barrier (BBB) is minimal and no antagonism is observed in the CNS receptors [49]. Several studies have shown that naloxone is effective in OBD [2,9,29,30,46]. The dose range used to reduce the incidence of OBD varies: an 8-10 mg dose [2], or 10-20% of the daily morphine dose [19,30].…”
Section: Opioid Antagonistsmentioning
confidence: 99%
“…Several studies have shown that naloxone is effective in OBD [2,9,29,30,46]. The dose range used to reduce the incidence of OBD varies: an 8-10 mg dose [2], or 10-20% of the daily morphine dose [19,30]. In order to prevent the opioid withdrawal syndrome (OWS) and slowly increase the amount of drug to obtain a satisfactory response, an initial maximum dose of 5 mg is recommended [47].…”
Section: Opioid Antagonistsmentioning
confidence: 99%